Invasive form of ciliated muconodular papillary tumor of the lung: A case report and review of the literature. Issue 9 (24th July 2018) - Miyai, Kosuke; Takeo, Hiroaki; Nakayama, Takefumi; Obara, Kiyohaya; Aida, Shinsuke; Sato, Kimiya; Matsukuma, Susumu
Abstract : We report a case of a 67‐year‐old woman with an invasive ciliated muconodular papillary tumor (CMPT) that developed in her right middle lobe. The current tumor was incidentally detected during a follow‐up imaging examination for a large cell carcinoma that was resected 10 years previously. Partial removal of the middle lobe showed a 2 cm‐sized, solid and myxoid tumor located in the peripheral region. Histologically, this tumor primarily consisted of ciliated columnar cells, mucous cells, and basal cells, all of which had relatively swollen nuclei and were proliferating in a lepidic or papillary/micropapillary manner. These features were consistent with those of previously reported CMPT. In addition, atypical spindle tumor cells with more swollen nuclei, which were partly continuous to less atypical basal tumor cells, were focally found and invaded fibrous stroma in a reticular fashion. Immunohistochemically, both basal cells and atypical spindle tumor cells were positive for pancytokeratin, cytokeratin 5/6, and p40. Increased p53 positivity was found in these invading spindle cells compared with basal tumor cells. Neither BRAF V600E nor V600K mutation was detected. We concluded that this tumor was an extremely rare invasive case of CMPT, possibly representing malignant transformation of basal tumor cell components of CMPT.